Prevalence of metabolic syndrome in workers of the mother-child center Miguel Grau, Chaclacayo, Peru - Soto Pascual, Melissa (2015)
Introduction: Chronic diseases in Peru are increasing at alarming rate and the metabolic syndrome (MS) follows the same trend. Faced with this problem the health team must play a role in education and prevention. Objectives: To determine the prevalence of metabolic syndrome in workers of a primary health care center and to examine its relationship with sociodemographic variables and body mass index (BMI). Design: Cross-sectional study. Location: Maternal Child Center (WCC) Miguel Grau, DISA IV Lima Este, Peru. Participants: Health workers. Interventions: All 108 workers who gave informed consent were surveyed for demographic data, and weight, height, waist circumference and blood pressure were obtained. In a 5 mL serum sample fasting blood glucose and lipid profile were determined. Descriptive statistics and U-Mann Whitney, Kruskal Wallis and chi2 tests were done; P value of 0.05 was used to determine significance. Main outcome measures: Metabolic syndrome, lipid profile, BMI categories, glycemia, number of risk factors. Results: 35.2% of workers had metabolic syndrome. SM was associated with age and BMI. No association was found with gender or occupational group. Conclusions: One-third of workers at the WCC Miguel Grau had MS, higher rate than in the Peruvian population.